Strengthening Student Character Education through Interdisciplinary Project-Based Learning Approaches - Annisa Helvina; Alfiana Alfiana; Haerul Mizan; Rafael Goh Zhi Hao (Gema Cendekia Institute, 2025)
Character education has become an essential focus in contemporary educational systems, as schools are increasingly expected to develop students’ moral, social, and civic competencies alongside academic achievement. This study investigates the effectiveness of interdisciplinary Project-Based Learning (PBL) as an instructional approach for strengthening student character education in formal school settings. Employing a mixed-methods, quasi-experimental design, the research involved an experimental group receiving interdisciplinary PBL instruction and a control group taught using conventional methods. Quantitative data were collected through character education questionnaires, learning outcome assessments, and 21st-century skills scales administered before and after the intervention, while qualitative data were obtained through classroom observations, student reflection journals, and semi-structured interviews. The findings indicate that students who participated in interdisciplinary PBL demonstrated significant improvements in key character dimensions, including responsibility, collaboration, creativity, independence, and civic awareness, compared to students in the control group. Additionally, interdisciplinary PBL was found to support academic learning and the development of critical thinking, communication, and problem-solving skills. Qualitative findings further revealed that students perceived interdisciplinary projects as meaningful and engaging learning experiences that encouraged ethical behavior, teamwork, and reflective thinking. The study concludes that interdisciplinary Project-Based Learning is an effective pedagogical strategy for integrating character education within academic instruction. By aligning character development with interdisciplinary learning objectives, educators can foster holistic student development and better prepare learners for the social and ethical challenges of the 21st century.